2019
DOI: 10.3390/ijgi8120532
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Uncrewed Aircraft Systems’ Lidar Data Quality

Abstract: Uncrewed aircraft systems (UASs) with integrated light detection and ranging (lidar) technology are becoming an increasingly popular and efficient remote sensing method for mapping. Due to its quick deployment and comparatively inexpensive cost, uncrewed laser scanning (ULS) can be a desirable solution to conduct topographic surveys for areas sized on the order of square kilometers compared to the more prevalent and mature method of airborne laser scanning (ALS) used to map larger areas. This paper rigorously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…Herein, a simple accuracy assessment is provided. A rigorous accuracy assessment of the RAPID's UAS lidar can be found in Babbel et al (2019), which shows similar accuracy results to those presented in this case study. Ultimately, the ability to efficiently obtain data across the entire landslide, minimal time of mobilization, and overall quality of data made the UAS lidar the optimal choice for obtaining the post-event DEMs over alternatives such as terrestrial and airborne lidar and SfM/MVS photogrammetric methods.…”
Section: Case Study 2: Flowslide Mapping Following the 2018 Palu-dongsupporting
confidence: 77%
“…Herein, a simple accuracy assessment is provided. A rigorous accuracy assessment of the RAPID's UAS lidar can be found in Babbel et al (2019), which shows similar accuracy results to those presented in this case study. Ultimately, the ability to efficiently obtain data across the entire landslide, minimal time of mobilization, and overall quality of data made the UAS lidar the optimal choice for obtaining the post-event DEMs over alternatives such as terrestrial and airborne lidar and SfM/MVS photogrammetric methods.…”
Section: Case Study 2: Flowslide Mapping Following the 2018 Palu-dongsupporting
confidence: 77%
“…Many of these unmanned laser scanning (ULS) systems are still unreliable and at an experimental stage, operating lower-grade LiDAR sensors commonly used in robotics applications. However, recent studies based on UAVs equipped with dedicated mapping sensors demonstrated reliable collection of topographic datasets (Babbel et al, 2019;Mayr et al, 2019). ULS can produce accurate and very high spatial resolution point clouds, enabling more detailed characterisation of bare earth and microtopographic features.…”
Section: Monitoring River Morphologymentioning
confidence: 99%
“…There are also a great deal of missing spot height data, particularly in areas which workers with TS have failed to enter or observe [19,20]. Furthermore, if inexperienced surveyors undertake the surveys, the acquired data are vulnerable to human error [21], such as the instruments being in poor condition, obstacles from steep slopes [22] and a lack of entrance access to the field measurement site [20]. Topographic features are primarily non-automated and require many individuals to check and observe the data collection process [23].…”
Section: Introductionmentioning
confidence: 99%